Relações ecológicas e fitossociologia em remanescente florestal no escudo cristalino, bioma Pampa, RS - Silva Junior, José Carlos Corrêa da (2017)
The present work aimed to describe the floristic composition, the structure and the diversity of the arboreal component of a native forest fragment in an ecotonal zone between the Semidecidual Seasonal Forest, the Mixed Ombrophilous Forest and the fields of the Pampa biome, located in the municipality of Santana da Boa Vista, Rio Grande do Sul, a region belonging to the Crystalline Shield. And investigate the relationship between the arboreal component, the topography, the microclimatic variables and the environmental standards (edge and center). It was also sought to identify the formation of natural ecological filters related to environmental standards and gradients, and to perform the complementary environmental diagnosis by the analysis of associated species, besides determining the possible ecological relations between the presence of Psychotria sp. and the establishment of natural regeneration. For the characterization of the vegetation 27 sampling points were systematically demarcated along transects, being installed in each point three quadratic parcels with fixed area of 100 m2, in which two subplots of 1x1 m were arranged. In the plots, all tree individuals with CAP ≥ 15 cm were amostred, being determined species, CAP, height, counting the number of lianas per supporting tree and determining the degree of coverage by bryophytes, pteridophytes and epiphytes by the Braun-Blanquet method ( 1932), was also performed the counting of juvenile individuals of Podocarpus lambertii, Araucaria angustifolia and Bromelia antiachanta. In the subplots all the regenerating arboreal individuals were sampled and the degree of coverage per Psycotria sp. was determinated. Additionally, the environmental and microclimatic variables were obtained at all sampling points. For the analysis of the data, in addition to the phytosociological descriptors, correlation analysis were performed, CATPCA and Decision Trees. Was observed floristic singularity in the remnant. Some variables tended to express typical characteristics of Mixed Ombrophilous Forest, while others, characteristic of Semidecidual Seasonal Forest, highlighting the ecotonal character and the importance of conservation of these formations, with respect to the maintenance of genetic diversity. For the arboreal component stood out Podocarpus lambertii, Casearia sylvestris, Nectandra megapotamica and Gymnanthes Klotzschiana. The remnant presented greater floristic similarity with the Semidecidual Seasonal Forest despite the marked presence of Podocarpus lambertii. No evidence was found that the Psychotria sp. is negatively influencing the natural regeneration of the tree species, being observed indicative of a regular rate of recruitment in all the groups considered in the regeneration analysis. The environmental variables showed influence on the composition and abundance of the arboreal component and of the regeneration. The remnant presented a high density of cover of associated species indicating the high support capacity of the environment, which, despite some occasional differences, did not demonstrate the existence of marked edge gradients, nor indicative of deleterious effects due to overexploitation or frequent disturbances. The standard of uniformity of individuals among tree species and the non-existence of dominance by a specific group, together with the marked presence of species associated, both animals and plants, also reinforce typical characteristics of mature forests with a good stage of conservation, where the dynamic equilibrium is the agent of ecosystemic molding.